2009
DOI: 10.1149/1.3242513
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nitrogen Concentration on Nanodiamond Film Characteristics for Electrode Application

Abstract: Microwave plasma chemical vapor deposition was used to fabricate nanodiamond films. Nitrogen incorporation was achieved by the introduction of N2 gas along with H2 and CH4 gases in the plasma. SEM studies revealed a change in the microstructure with increase in the N2 flow rate, transitioning from a 'ridge'-like surface morphology to a more 'cauliflower'-like structure. X-ray photoelectron spectroscopy (XPS) analysis showed a general decrease in the sp3 hybridized carbon content while the sp2 hybridized carbon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Moreover, the microwave plasma (MW) CVD is widely used to synthesize ND films on various chemically dissimilar surface substrates owing to the relatively low growth temperature, which utilizes the microwave energy to heat and decompose the gas molecules in the cavity into reactive groups, then finally obtain a high-quality ND film [ 65 , 66 , 67 , 68 , 69 , 70 ]. For example, Cheng C.Y.…”
Section: Fabrication Methods and Nucleation Process Of Nanodiamond Filmmentioning
confidence: 99%
“…Moreover, the microwave plasma (MW) CVD is widely used to synthesize ND films on various chemically dissimilar surface substrates owing to the relatively low growth temperature, which utilizes the microwave energy to heat and decompose the gas molecules in the cavity into reactive groups, then finally obtain a high-quality ND film [ 65 , 66 , 67 , 68 , 69 , 70 ]. For example, Cheng C.Y.…”
Section: Fabrication Methods and Nucleation Process Of Nanodiamond Filmmentioning
confidence: 99%
“…Figure 3(b) shows the 'ridge' like microstructure of the nanodiamond film of each UME, see inset. Material characterization using Raman spectroscopy and X-ray Photoelectron Spectroscopy (XPS) and vacuum field emission studies from a similar planar nanodiamond film have been reported previously (24)(25). …”
Section: Sem Characterizationmentioning
confidence: 96%
“…The UMEs have a 'donut' shape, with a thick and raised edge and a slightly recessed part in the middle, as seen in the inset of figure 2(b). Material characterization using Raman spectroscopy and X-ray Photoelectron Spectroscopy (XPS) of the nanodiamond film has been reported previously (33)(34). In this work, a scan rate of 300V/s was applied and repeated at a frequency of 10Hz, which simulates sub-second transient events of DA release in the brain (18)(19)(20)(21)(22).…”
Section: Sem Characterizationmentioning
confidence: 99%